The Relationship Between Stress Levels and Neck Pain: A Literature Review - Nurul Aulia Pohan; Ni Made Swasti Wulanyani; I Gusti Ayu Putu Wulan Budisetyani (Journal of Community Health Provision, 2026)
Neck pain is a common musculoskeletal complaint, especially in individuals who engage in activities involving prolonged static body positions. In addition to physical factors, psychological factors such as stress can also influence the onset of neck pain. Stress can increase muscle tension and modulate pain perception, potentially worsening neck complaints. This study aims to examine the relationship between stress levels and the incidence of neck pain through a systematic literature review. The literature search was conducted in March 2026 through PubMed, ScienceDirect, and Google Scholar with publications spanning 2021–2026. The selected articles were peer-reviewed studies relevant to the topic. Based on the PRISMA flow, five articles met the criteria for in-depth analysis. The results of the study indicate that individuals with higher stress levels tend to experience more severe neck pain. Influencing factors include muscle tension, changes in pain perception, non-ergonomic posture, and psychosocial factors such as academic pressure and workload. In conclusion, stress can significantly influence the onset of neck pain. These findings emphasize the importance of understanding the relationship between psychological and physical factors, such as stress management, posture, and ergonomics education, as a basis for designing more effective neck pain prevention strategies.